Process for forming biodegradable resin composite disposable tableware

CN122898152APending Publication Date: 2026-10-13SHANDONG QILECAI NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611316186.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]然而,如何在完全不添加外源偶联剂、相容剂或涂层材料的条件下,仅利用植物纤维自身固有的木质素组分,通过工艺手段将其活化为界面增容介质,同步实现纤维与纤维之间的焊接以及纤维与生物降解树脂之间的化学键合,从而解决纤维与树脂的界面不相容问题——这一技术问题在上述现有技术中均未得到解决,在行业内仍属空白

Benefits of technology

一、本发明通过调控混合纤维的总木质素含量,采用饱和水蒸气湿热预处理使纤维自身固有的木质素从细胞壁内部迁移至表面并形成活化富集层,再经热压模压使活化木质素同时与生物降解树脂发生酯交换反应和与相邻纤维表面木质素发生缩合反应,能够在完全不添加外源偶联剂、相容剂或胶黏剂的条件下,形成纤维树脂化学键合界面和纤维间木质素焊接节点,有效解决了植物纤维与生物降解树脂之间界面不相容的技术问题,明显提升了复合材料的力学性能,同时避免了外源化学品引入带来的食品安全隐患和额外成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898152A_ABST
    Figure CN122898152A_ABST
Patent Text Reader

Abstract

The application discloses a biodegradable resin composite disposable tableware forming process and relates to the technical field of environment degradable materials.The process mixes high-lignin-content plant fibers with low-lignin-content plant fibers to obtain mixed fibers with a suitable total lignin content, carries out saturated water vapor moist heat pretreatment to make lignin migrate to the surface of the fibers to form an activated lignin enrichment layer, mixes the activated lignin enrichment layer with biodegradable resin particles, and then carries out hot-pressing and die-pressing forming, so that the activated lignin simultaneously undergoes ester exchange reaction with the resin and condensation reaction with adjacent fibers to form a double-interface reinforced structure.The application does not need to add any exogenous coupling agent, compatilizer or adhesive, the prepared tableware has excellent mechanical properties, can be completely biodegraded, has low raw material cost, and has a simple process and is suitable for industrialized production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmentally degradable materials technology, specifically to a molding process for disposable tableware made of biodegradable resin composites. Background Technology

[0002] Disposable plastic tableware is widely used due to its low cost and convenience, but its slow degradation has caused serious environmental pollution and microplastic hazards. Biodegradable resins, such as polylactic acid, polybutylene adipate terephthalate, and polybutylene succinate, are considered ideal materials to replace traditional plastics, but pure resin tableware has drawbacks such as high cost and insufficient heat resistance. Composites of plant fibers with biodegradable resins can reduce raw material costs and improve the rigidity of products by utilizing the skeletal support of the fibers, making this an important technological direction in this field.

[0003] In existing technologies, the composite process of plant fibers and biodegradable resins generally faces the problem of poor interfacial bonding between the fibers and resins. Because plant fibers are hydrophilic due to their rich hydroxyl content, while biodegradable resins are mostly hydrophobic polyesters, the two are thermodynamically incompatible. Simple melt blending results in only a physical encapsulation relationship between the fibers and resins, and the mechanical properties of the composite material decrease sharply when the fiber content exceeds 15%. Therefore, existing technologies typically use external coupling agents or compatibilizers to improve interfacial bonding, such as adding silane coupling agents or maleic anhydride-grafted polylactic acid. Patent publication number CN108582337A discloses a method for the explosive separation and self-recombination of bamboo. Without removing lignin or adding adhesives, steam explosion treatment is used to separate the cellulose, hemicellulose, and lignin of bamboo. Then, high-temperature molding causes physicochemical changes in the components, resulting in self-gluing and recombination of the bamboo fibers to form a glue-free fiber composite material. This method belongs to the "pure fiber self-gluing" route and does not involve interfacial welding and compatibilization between plant fibers and biodegradable resins. Another existing technology proposes a lignin-driven fiber welding and PHB conformal coating synergistic modification technique. This technique increases the phenolic hydroxyl and carboxyl group content of residual lignin in the fiber through chemical pretreatment to enhance its reactivity. Hot pressing causes the residual lignin to soften, redistribute, and self-crosslink, and then co-melts with PHB at the interface to form a biodegradable oil-resistant surface layer. In this scheme, PHB is an essential coating component, undertaking the main function of constructing the surface barrier layer.

[0004] However, the technical problem of solving the interfacial incompatibility between fibers and resins—which requires no external coupling agents, compatibilizers, or coating materials, and relies solely on the inherent lignin components of plant fibers to activate them into an interfacial compatibilizing medium through processing methods—remains unresolved in the aforementioned existing technologies and remains a gap in the industry. This invention presents a solution to this technical challenge. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a molding process for disposable tableware made of biodegradable resin composites. By controlling the total lignin content of the mixed fibers, the lignin of the fibers is activated by saturated steam wet heat pretreatment, and then the activated lignin is mediated to form a double interface reinforcement structure through hot pressing. This process can solve the interfacial incompatibility problem between plant fibers and biodegradable resins without adding exogenous coupling agents or compatibilizers, and produce high-performance biodegradable disposable tableware.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a molding process for disposable tableware made of biodegradable resin composite, the process comprising the following steps: Step 1: Mix high-lignin-content plant fibers with low-lignin-content plant fibers to obtain mixed fibers. The high-lignin-content plant fibers have a lignin content of not less than 25 wt%, the low-lignin-content plant fibers have a lignin content of 10 wt%-15 wt%, and the total lignin content in the mixed fibers is 18 wt%-22 wt%. Step 2: The mixed fibers are subjected to wet heat pretreatment in a saturated water vapor environment at 120℃-140℃ for 20min-40min, so that the lignin in the mixed fibers migrates from the inside of the fiber cell wall to the fiber surface and forms an activated lignin enrichment layer on the fiber surface. Step 3: The pre-treated mixed fibers are mixed with biodegradable resin particles and then laid into the mold cavity. Hot pressing is performed at a mold temperature of 180℃-210℃ and a molding pressure of 8MPa-15MPa for 60s-120s. This allows the biodegradable resin particles to melt and wet the fiber surface. At the same time, the lignin in the activated lignin enrichment layer on the fiber surface undergoes an ester exchange reaction with the biodegradable resin and a lignin condensation reaction occurs at the contact points of adjacent fibers, forming a fiber-resin chemical bonding interface and lignin welding nodes between fibers, resulting in disposable tableware products.

[0007] By mixing plant fibers with high and low lignin content and controlling the total lignin content to 18wt%-22wt%, and then pre-treating with saturated steam, the lignin within the fibers migrates from the cell walls to the fiber surface, forming an activated lignin-rich layer. Finally, during hot pressing, this activated lignin undergoes both transesterification with the molten biodegradable resin and condensation with the lignin on the surface of adjacent fibers. This allows for the establishment of a chemical bond interface between the fibers and resin using the inherent lignin components of the fibers, without the addition of any exogenous coupling agents, compatibilizers, or adhesives, and the formation of lignin weld joints at the contact points of adjacent fibers. This dual-interface reinforcement mechanism enables the composite material to achieve a flexural strength of 55MPa-75MPa with a fiber content of 25wt%-35wt%.

[0008] Furthermore, in step one, the high lignin content plant fiber is one or more of palm fiber, coconut shell fiber, and sugarcane bagasse fiber, and the low lignin content plant fiber is one or more of wheat straw fiber, rice straw fiber, and corn stalk fiber.

[0009] By selecting one or more of palm fiber, coconut shell fiber, and sugarcane bagasse fiber as high-lignin-content fiber sources, and one or more of wheat straw fiber, rice straw fiber, and corn stalk fiber as low-lignin-content fiber sources, these fibers are all major agricultural by-products or wastes, with wide availability and low prices. Palm fiber has a lignin content of 28wt%-35wt%, and coconut shell fiber has a lignin content of 30wt%-38wt%, providing sufficient inherent lignin reserves for wet heat pretreatment. This ensures the formation of a continuous and dense activated lignin-rich layer on the fiber surface, thus providing ample reactant sources for the lignin-mediated interfacial welding reaction during subsequent molding.

[0010] Furthermore, in step one, the mass ratio of the high-lignin-content plant fiber to the low-lignin-content plant fiber is 1:1.5-1:2.5.

[0011] By controlling the mass ratio of high-lignin-content plant fibers to low-lignin-content plant fibers at 1:1.5-1:2.5, the total lignin content of the mixed fiber system is stabilized between 18wt% and 22wt%. When the proportion of high-lignin fibers is too high, the lignin release during wet heat pretreatment is excessive, and some free lignin will be lost into the pretreatment wastewater, resulting in a waste of activated lignin. When the proportion of high-lignin fibers is too low, the amount of activated lignin enriched on the fiber surface is insufficient to form an effective and continuous interfacial welding layer, leading to inadequate welding. This ratio range balances the sufficient supply and effective utilization of activated lignin, ensuring sufficient chemical bonding at the fiber-resin interface while avoiding raw material waste and wastewater treatment burden caused by excessive lignin loss.

[0012] Furthermore, in step three, the biodegradable resin particles are one or more of polylactic acid, polybutylene adipate terephthalate, polybutylene succinate, and polyhydroxyalkanoate.

[0013] By employing one or more of polylactic acid, polybutylene adipate terephthalate, polybutylene succinate, and polyhydroxyalkanoates as the biodegradable resin matrix, all of which are industrially produced biodegradable polyesters with hydroxyl and carboxyl active end groups at the ends of their molecular chains, these active end groups can undergo transesterification reactions with the phenolic and alcoholic hydroxyl groups in the activated lignin-rich layer on the fiber surface, forming lignin-resin covalent ester bonds. These covalent bonds anchor one end of the lignin molecule to the fiber and the other end to the resin molecular chain, constituting a chemical bridging structure between the fiber and resin, which is the molecular basis for achieving chemical bonding at the fiber-resin interface.

[0014] Furthermore, in step three, the biodegradable resin particles are a composition of polylactic acid and polybutylene adipate terephthalate, with a mass ratio of polylactic acid to polybutylene adipate terephthalate of 55:45-75:25.

[0015] By employing a composition of polylactic acid (PLA) and polybutylene adipate terephthalate (PAT) in a mass ratio controlled between 55:45 and 75:25, the combined requirements for rigidity and toughness in the finished product can be met. PLA provides high flexural modulus and surface hardness, giving the tableware good stiffness during use; PAT provides excellent elongation at break and impact toughness, making the tableware less prone to breakage when subjected to bending and drop impacts. Within this ratio range, the melt viscosity of both resins is well-matched, allowing for simultaneous melting and uniform wetting of the fiber surface during molding. This ensures sufficient contact between the activated lignin-rich layer on the fiber surface and both resins, facilitating transesterification.

[0016] Furthermore, in step three, the amount of the biodegradable resin particles used is 25wt%-50wt% of the oven-dry weight of the mixed fibers.

[0017] By controlling the amount of biodegradable resin particles to 25wt%-50wt% of the oven-dry weight of the mixed fibers, the proportion of natural plant fibers can be maximized while ensuring the mechanical properties and molding flowability of the product. When the resin content is below 25wt%, the amount of molten resin is insufficient to fully wet the entire fiber surface, resulting in dry spots and delamination defects in the product. When the resin content is above 50wt%, the synthetic resin content is too high, which is not conducive to reducing raw material costs and reducing dependence on fossil resources. This dosage range allows for sufficient interfacial contact area between the fiber and resin, providing a sufficient reaction interface for lignin-mediated interfacial transesterification reactions.

[0018] Furthermore, in step two, the pressure of the wet heat pretreatment is 0.2 MPa-0.4 MPa; and the moisture content of the mixed fiber after wet heat pretreatment is 25 wt%-40 wt%.

[0019] By controlling the wet heat pretreatment pressure at 0.2MPa-0.4MPa and the moisture content of the pretreated mixed fibers at 25wt%-40wt%, sufficient depolymerization, activation, and migration of lignin within the fiber cell walls can be ensured. A saturated vapor pressure of 0.2MPa-0.4MPa corresponds to a treatment temperature of 120℃-140℃. This temperature range allows for the selective cleavage of the β-O-4 ether bonds in lignin, releasing phenolic hydroxyl active sites while maintaining the integrity of the cellulose and hemicellulose matrix. The 25wt%-40wt% moisture content of the pretreated fibers provides the necessary water-catalyzed environment for the lignin transesterification reaction in the subsequent hot-pressing stage, while avoiding porosity defects caused by excessive moisture content or inadequate interfacial reactions due to insufficient moisture content.

[0020] Furthermore, the mixed fibers have a fiber length of 0.5mm-5mm, a fiber diameter of 10μm-100μm, and a fiber aspect ratio of 20-200.

[0021] By controlling the fiber length of the mixed fibers to 0.5mm-5mm, the fiber diameter to 10μm-100μm, and the fiber aspect ratio to 20-200, an effective three-dimensional overlapping network skeleton can be formed during the compression molding process. When the fiber length is <0.5mm, the aspect ratio is insufficient, the number of overlapping points between fibers is reduced, and a continuous and effective stress transfer network cannot be formed; when the fiber length is >5mm, the fibers are prone to entanglement and agglomeration, resulting in uneven material distribution in the mold cavity, leading to local density differences and inconsistent mechanical properties in the product. This fiber morphology range takes into account both the fiber network overlapping effect and the uniformity of material distribution, allowing lignin welding nodes to be fully formed at the contact points of fiber overlap.

[0022] Furthermore, in step three, during the mixing of the mixed fibers and the biodegradable resin particles, a processing aid not exceeding 3 wt% of the total mass of the raw materials is added. The processing aid is one or more of the following: calcium stearate, zinc stearate, vitamin E, rosemary extract, glycerin, and triethyl citrate.

[0023] By selectively adding no more than 3 wt% of calcium stearate, zinc stearate, vitamin E, rosemary extract, glycerol, or triethyl citrate as processing aids, processing performance can be improved without affecting the core mechanism of lignin interfacial welding. Stearate aids can reduce the coefficient of friction between the melt and the mold surface, reducing demolding resistance; vitamin E and rosemary extract can inhibit excessive oxidation of lignin during high-temperature processing, protecting its reactivity; glycerol and triethyl citrate can provide auxiliary plasticization to activated lignin, lowering its glass transition temperature. All of the above aids are food-grade or of natural origin, meeting the food safety requirements for disposable tableware, and none are essential components for achieving interfacial welding.

[0024] Furthermore, after the hot-press molding in step three, a fourth step is also included: The demolded product is then subjected to post-curing treatment at 110℃-140℃ for 30-60 minutes. After the post-curing treatment, a food-grade nano wax emulsion with a solid content of 3wt%-5wt% is sprayed onto the surface of the product, with a spraying amount of 0.5g / m²-1.5g / m², forming a hydrophobic wax film with a thickness of 1μm-3μm. The food-grade nano wax emulsion is a food-grade palm wax emulsion or a food-grade carnauba wax emulsion.

[0025] By performing a post-curing treatment at 110℃-140℃ after hot pressing molding, the incomplete lignin cross-linking reaction within the mold can continue to complete under normal pressure, further improving the bending strength of the product by 10%-20% and reducing water absorption by 15%-25%. After the post-curing treatment, a food-grade nano-carnauba wax emulsion or carnauba wax emulsion with a solid content of 3wt%-5wt% is sprayed at a rate of 0.5g / m²-1.5g / m², forming an ultra-thin hydrophobic wax film with a thickness of 1μm-3μm on the surface of the product, increasing the water contact angle of the product to over 100°. This wax film is a natural plant wax that can biodegrade along with the tableware body, producing no microplastic residue, and is suitable for bowls and containers for holding soup-based foods.

[0026] Compared with existing technologies, this biodegradable resin composite disposable tableware molding process has the following advantages: I. This invention regulates the total lignin content of mixed fibers and uses saturated steam wet heat pretreatment to allow the inherent lignin of the fibers to migrate from the cell wall to the surface and form an activated enrichment layer. Then, through hot pressing, the activated lignin undergoes both ester exchange reaction with biodegradable resin and condensation reaction with the lignin on the surface of adjacent fibers. This allows the formation of a chemical bond interface between fibers and resin and lignin welding nodes between fibers without the addition of any exogenous coupling agents, compatibilizers, or adhesives. This effectively solves the technical problem of interfacial incompatibility between plant fibers and biodegradable resin, significantly improves the mechanical properties of the composite material, and avoids the food safety hazards and additional costs caused by the introduction of exogenous chemicals.

[0027] II. This invention uses abundant agricultural by-products as plant fiber raw materials, which are widely available and inexpensive, effectively reducing the overall production cost of biodegradable disposable tableware. The process is simple and controllable, and the equipment used is conventional and general-purpose equipment in the field of composite material processing, requiring no special customization or modification. It is suitable for large-scale industrial continuous production. The prepared products are completely biodegradable in the natural environment, producing no microplastic residues, while possessing good performance and barrier properties, meeting the actual usage needs of various disposable tableware. Other advantages, objectives, and features of this invention will be set forth in part in the description which follows, and in part will be obvious to those skilled in the art based on the following examination, or may be taught from practice of the invention. Attached Figure Description

[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0029] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation

[0030] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below. Example

[0031] This embodiment discloses a specific implementation method for molding disposable tableware using biodegradable resin composites. Palm fiber is used as a high-lignin-content plant fiber, and wheat straw fiber as a low-lignin-content plant fiber. By controlling the fiber ratio, a mixed fiber with a total lignin content of 20wt% is obtained. The fiber is pretreated with saturated steam at 130℃ for 30 minutes to allow lignin to migrate to the fiber surface, forming an activated lignin-rich layer. This layer is then mixed with composite resin particles of polylactic acid, polyadipate, and butylene terephthalate. The mixture is then hot-pressed at a mold temperature of 195℃ and a molding pressure of 12MPa for 90 seconds. Finally, post-curing and food-grade nano-wax emulsion spraying are performed to obtain the disposable bowl product. This embodiment fully demonstrates the entire process from raw material pretreatment to finished product preparation, clarifying the operation methods, equipment requirements, and key process parameters for each step. It verifies the feasibility of using the fiber's own lignin to achieve interface reinforcement. The prepared bowl achieves a bending strength of 68MPa, a water absorption rate of 8.2%, and a water contact angle of 108°, fully meeting the requirements for disposable tableware.

[0032] Specifically, the raw materials used in this embodiment are all commercially available industrial-grade products, and the equipment used is all conventional equipment in the field of composite material processing, requiring no special customization. During implementation, the fluctuation range of each process parameter is strictly controlled to ensure the stability and consistency of product performance. The products prepared in this embodiment are completely biodegradable in the natural environment, do not produce microplastic pollution, and the raw material cost is more than 35% lower than that of pure biodegradable resin tableware, showing good prospects for industrial application.

[0033] This embodiment uses the preparation of a disposable round bowl with a diameter of 150mm and a depth of 50mm as an example to illustrate in detail the specific implementation steps of the molding process for disposable tableware made of biodegradable resin composite. To more intuitively demonstrate the complete process flow from raw material preparation to finished product preparation, and the lignin-mediated dual interface enhancement mechanism, please refer to [link to relevant documentation]. Figure 1 .

[0034] First, the raw materials were prepared and pretreated. Commercially available palm fiber with a lignin content of 32 wt% was selected as the high-lignin-content plant fiber. Commercially available wheat straw fiber with a lignin content of 12 wt% was selected as the low-lignin-content plant fiber. The palm fiber and wheat straw fiber were coarsely pulverized in a pulverizer, then screened through a vibrating screen to remove excessively long fibers and fine dust, collecting fiber segments with a length of 0.5 mm to 5 mm. The screened palm fiber and wheat straw fiber were then separately fed into an air classifier to remove impurities and light components, obtaining pure single fibers. The diameter and length of the fibers were measured using an optical microscope. The average diameter of the palm fiber was 45 μm, the average length was 2.2 mm, and the aspect ratio was 49; the average diameter of the wheat straw fiber was 28 μm, the average length was 1.8 mm, and the aspect ratio was 64. Both fibers have aspect ratios within the range of 20-200, enabling them to form an effective three-dimensional overlapping network during subsequent molding. Palm fiber and wheat straw fiber were weighed at a mass ratio of 1:2 and mixed in a double cone mixer for 20 minutes to obtain mixed fibers. The total lignin content of the mixed fibers was measured and found to be 20 wt%, meeting the process requirements. Maintaining the total lignin content of the mixed fibers between 18 wt% and 22 wt% ensures sufficient reactants for subsequent interfacial reactions while avoiding excessive lignin loss that would lead to raw material waste and wastewater treatment burden.

[0035] Next, a wet heat pretreatment of the mixed fibers is performed. The mixed fibers are placed in a stainless steel mesh basket and then placed in a horizontal steam explosion reactor. The reactor door is closed and sealed, and saturated steam is introduced into the reactor. The temperature and pressure are slowly increased to 130℃ and 0.3MPa, and maintained at this temperature and pressure for 30 minutes. During the pretreatment, the saturated steam penetrates into the fiber cell wall, causing selective cleavage of the β, O, and 4 ether bonds of lignin, releasing a large number of phenolic hydroxyl active sites. At the same time, lignin molecules depolymerize, increasing their fluidity and gradually migrating from the cell wall to the fiber surface. After the pretreatment, the exhaust valve is quickly opened to release the pressure, and the fibers are removed. At this point, the water content of the mixed fibers is 32wt%. This water content provides the necessary water catalytic environment for the transesterification reaction in the subsequent hot pressing process, while avoiding the formation of porosity defects during molding due to excessive water content.

[0036] The wet heat pretreatment equipment in this embodiment mainly consists of a steam generator, a steam explosion reactor, a temperature control system, and a pressure control system. Saturated steam generated by the steam generator is piped into the steam explosion reactor. Temperature and pressure sensors monitor the temperature and pressure inside the reactor in real time and transmit the signals to the control system, enabling precise control of the pretreatment process. The stainless steel mesh basket is made of 304 stainless steel with a mesh size of 2mm, ensuring sufficient contact between the steam and the fibers while preventing fiber loss.

[0037] Then, hot pressing molding is performed. The biodegradable resin particles are a combination of polylactic acid (PLA) and poly(adipate-butyl terephthalate), specifically Polylactic acid grade 4032D and Poly(adipate-butyl terephthalate) grade EcoflexFBlendC1200. PLA and Poly(adipate-butyl terephthalate) are weighed at a mass ratio of 65:35 and melt-blended in a twin-screw extruder at an extrusion temperature of 170℃-190℃ and a screw speed of 150 r / min. The blend is then water-cooled and pelletized to obtain composite resin particles with a particle size of 2mm-4mm. The mass ratio of PLA to Poly(adipate-butyl terephthalate) is controlled between 55:45 and 75:25 to balance the rigidity and toughness of the product while ensuring a match in the melt viscosity of the two resins, allowing for simultaneous melting and uniform wetting of the fiber surface during molding.

[0038] Weigh out the pretreated mixed fibers and composite resin particles according to a ratio of 35 wt% of the oven-dry weight of the mixed fibers. Place both in a high-speed mixer and mix for 15 minutes at a speed of 800 rpm. During mixing, add 0.8 wt% calcium stearate and 0.5 wt% vitamin E as processing aids, with the total amount of processing aids not exceeding 3 wt% of the total raw material weight. Calcium stearate reduces the coefficient of friction between the melt and the mold surface, decreasing demolding resistance; vitamin E inhibits excessive oxidation of lignin during high-temperature processing, protecting its reactivity. All the above aids are food-grade substances, meeting the food safety requirements for disposable tableware.

[0039] The mixed material is evenly spread into the cavity of a bowl mold preheated to 195℃, with a spreading amount of 35g. The mold is made of 45# steel with a polished surface and a cavity surface roughness of Ra0.8μm. After the mold is closed, the hydraulic press is started, and the pressure is slowly increased to 12MPa at a speed of 5mm / s, and held at this pressure for 90s. During the hot pressing process, the composite resin particles melt under heat and fully wet the fiber surface under pressure. At the same time, the lignin molecules in the activated lignin enrichment layer on the fiber surface undergo transesterification with the hydroxyl and carboxyl groups at the ends of the molten resin molecular chains, forming lignin-resin covalent ester bonds, which constitute a chemical bridging structure between the fiber and the resin. At the contact points of adjacent fibers, condensation reactions occur between activated lignin molecules, forming lignin welding nodes that firmly connect the fibers together.

[0040] After the pressure holding period, the cooling water system is turned on to cool the mold. When the mold temperature drops below 60℃, the mold is opened and the formed bowl product is removed. The demolding process is smooth, and the product surface is smooth without defects such as sticking, missing material, or delamination.

[0041] Next, a post-curing treatment is performed. The demolded bowls are placed in a hot air circulating oven and kept at 125°C for 45 minutes. The post-curing treatment allows the incomplete lignin cross-linking reaction within the mold to continue under normal pressure, further improving the mechanical properties of the product and reducing water absorption. After post-curing, the product is removed and allowed to cool naturally to room temperature.

[0042] Finally, a hydrophobic surface treatment is performed. Food-grade carnauba wax emulsion is diluted with deionized water to a solid content of 4 wt%, stirred thoroughly, and poured into the spray gun's container. The wax emulsion is then evenly sprayed onto the inner and outer surfaces of the bowl using an air spraying method. The spraying pressure is 0.2 MPa, the spraying distance is 20 cm, and the spraying amount is 1.0 g / m². After spraying, the bowl is placed in a 60°C oven to dry for 10 minutes, allowing the moisture in the wax emulsion to completely evaporate, forming a hydrophobic wax film approximately 2 μm thick on the surface. This wax film is a natural plant wax that can biodegrade along with the tableware, leaving no microplastic residue and effectively improving the product's waterproof and oil-resistant properties.

[0043] The disposable bowls prepared in this embodiment were subjected to performance tests, and all test methods adopted relevant national standards. Bending strength was tested according to GB / T9341, 2008 "Determination of Bending Properties of Plastics", with a sample size of 80mm × 10mm × 4mm and a testing speed of 2mm / min. Water absorption was tested according to GB / T1034, 2008 "Determination of Water Absorption of Plastics", by immersing the sample in distilled water at 23℃ for 24 hours and calculating the water absorption rate. Water contact angle was tested using a contact angle measuring instrument, with deionized water as the test liquid and a test temperature of 25℃.

[0044] Test results show that the bowl prepared in this embodiment has a flexural strength of 68 MPa, a flexural modulus of 3.2 GPa, and an elongation at break of 5.8%, exhibiting good rigidity and toughness, and can withstand loads during normal use. Its water absorption rate of 8.2% is far lower than that of pure plant fiber tableware, effectively preventing soup penetration. With a water contact angle of 108°, it possesses good hydrophobic properties and is suitable for holding various hot and cold foods.

[0045] The product was placed in natural soil for degradation tests. After 6 months, the product's mass loss rate reached 72%, and after 12 months, it was completely degraded, meeting the requirements for biodegradable materials.

[0046] This embodiment fully implements the molding process of disposable tableware made from biodegradable resin composites. By controlling the ratio of plant fibers with high lignin content to those with low lignin content, a mixed fiber with an appropriate total lignin content is obtained. After saturated steam heat pretreatment, the lignin from the fibers migrates to the surface, forming an activated lignin-rich layer. During hot pressing, the activated lignin undergoes both transesterification with the biodegradable resin and condensation with the lignin on the surface of adjacent fibers, forming a chemically bonded interface between the fiber and resin, and lignin welding nodes between the fibers. This process does not add any exogenous coupling agents, compatibilizers, or adhesives; it only utilizes the inherent lignin components of the fibers to achieve interface reinforcement, solving the technical problem of interfacial incompatibility between plant fibers and biodegradable resin.

[0047] The raw materials used in this embodiment are all bulk agricultural by-products and industrially produced biodegradable resins, which are widely available and inexpensive. The equipment used is all conventional equipment in the field of composite material processing, and the process parameters are easy to control, making it suitable for large-scale industrial production. The prepared products have excellent mechanical properties, good waterproof and oil-proof performance, and are completely biodegradable. At the same time, the raw material cost is significantly lower than that of pure biodegradable resin tableware, resulting in good economic and environmental benefits.

[0048] This embodiment verifies the feasibility and superiority of the technical solution of the present invention, providing a solid foundation for the industrial application of the present invention. In actual production, the process parameters can be appropriately adjusted according to the shape and performance requirements of different tableware products to obtain the best product performance.

[0049] To further verify the rationality and necessity of the key process parameters of this invention, the following comparative examples were set up. Except for adjusting the total lignin content of the mixed fibers to the scope of this invention, the selection of raw materials, equipment specifications, operating steps, and process parameters in the comparative examples are completely consistent with the aforementioned examples.

[0050] Palm fiber and wheat straw fiber were weighed at a mass ratio of 1:3.5 and mixed in a double cone mixer for 20 minutes to obtain mixed fibers. The total lignin content of the mixed fibers was measured and found to be 15 wt%. The mixed fibers were then placed in a stainless steel mesh basket and placed in a horizontal steam explosion reactor for wet heat pretreatment at 130℃ and 0.3 MPa for 30 minutes. After pretreatment, the fibers were removed, and the moisture content of the mixed fibers was 31 wt%. The pretreated mixed fibers and composite resin particles were weighed according to a ratio of 35 wt% of the oven-dry weight of the mixed fibers. 0.8 wt% calcium stearate and 0.5 wt% vitamin E were added, and the mixture was placed in a high-speed mixer and mixed for 15 minutes. The mixed material was evenly spread into a bowl mold cavity preheated to 195℃, with a spreading amount of 35 g. After mold closing, the pressure was increased to 12 MPa and held for 90 seconds. After the pressure holding period, the product is cooled and demolded. It is then placed in a hot air circulating oven and kept at 125°C for 45 minutes for post-curing. Finally, a food-grade carnauba wax emulsion with a solid content of 4wt% is sprayed onto the surface of the product at a rate of 1.0 g / m². After drying, the comparison bowl product is obtained.

[0051] The performance of the bowls prepared in the comparative example was tested under the same conditions. The test results showed that the comparative product had a flexural strength of 42 MPa, a flexural modulus of 2.1 GPa, an elongation at break of 3.6%, a water absorption rate of 12.7%, and a water contact angle of 105°. The comparative product was prone to bending and breakage during use, and slight leakage occurred after 1 hour when filled with soup, failing to meet the normal use requirements of disposable tableware.

[0052] The key parameters and core performance indicators of the foregoing embodiments and comparative embodiments are summarized as follows: The above comparative results show that when the total lignin content of the mixed fibers is lower than the 18wt%-22wt% range of this invention, the enrichment of activated lignin on the fiber surface is insufficient, making it impossible to form a continuous and effective interfacial welding layer and chemical bonding interface. This results in a significant decrease in the mechanical properties of the composite material and a significant increase in water absorption. The total lignin content range determined by this invention through numerous experiments is a necessary condition for realizing the dual interfacial reinforcement mechanism of lignin welding between fibers and chemical bonding between fibers and resin. This ensures that the product simultaneously possesses excellent mechanical and barrier properties, meeting the requirements for disposable tableware.

[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A molding process for disposable tableware made of biodegradable resin composite, characterized in that, The process includes the following steps: Step 1: Mix high-lignin-content plant fibers with low-lignin-content plant fibers to obtain mixed fibers. The high-lignin-content plant fibers have a lignin content of not less than 25 wt%, the low-lignin-content plant fibers have a lignin content of 10 wt%-15 wt%, and the total lignin content in the mixed fibers is 18 wt%-22 wt%. Step 2: The mixed fibers are subjected to wet heat pretreatment in a saturated water vapor environment at 120℃-140℃ for 20min-40min, so that the lignin in the mixed fibers migrates from the inside of the fiber cell wall to the fiber surface and forms an activated lignin enrichment layer on the fiber surface. Step 3: The pretreated mixed fibers and biodegradable resin particles are mixed and laid into the mold cavity. Hot pressing is performed at a mold temperature of 180℃-210℃ and a molding pressure of 8MPa-15MPa for 60s-120s. This allows the biodegradable resin particles to melt and wet the fiber surface. At the same time, the lignin in the activated lignin enrichment layer on the fiber surface undergoes an ester exchange reaction with the biodegradable resin and a lignin condensation reaction occurs at the contact points of adjacent fibers, forming a fiber-resin chemical bonding interface and lignin welding nodes between fibers, resulting in disposable tableware products.

2. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, In step one, the high lignin content plant fiber is one or more of palm fiber, coconut shell fiber, and sugarcane bagasse fiber, and the low lignin content plant fiber is one or more of wheat straw fiber, rice straw fiber, and corn stalk fiber.

3. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, In step one, the mass ratio of the high lignin content plant fiber to the low lignin content plant fiber is 1:1.5-1:2.

5.

4. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, In step three, the biodegradable resin particles are one or more of polylactic acid, polybutylene adipate terephthalate, polybutylene succinate, and polyhydroxyalkanoate.

5. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, In step three, the biodegradable resin particles are a composition of polylactic acid and polybutylene adipate terephthalate, with a mass ratio of polylactic acid to polybutylene adipate terephthalate of 55:45-75:

25.

6. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, In step three, the amount of the biodegradable resin particles used is 25wt%-50wt% of the oven-dry weight of the mixed fibers.

7. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, In step two, the pressure of the wet heat pretreatment is 0.2 MPa-0.4 MPa; the moisture content of the mixed fiber after wet heat pretreatment is 25 wt%-40 wt%.

8. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, The mixed fibers have a fiber length of 0.5mm-5mm, a fiber diameter of 10μm-100μm, and a fiber aspect ratio of 20-200.

9. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, In step three, during the mixing of the mixed fibers and the biodegradable resin particles, a processing aid not exceeding 3 wt% of the total mass of the raw materials is added. The processing aid is one or more of the following: calcium stearate, zinc stearate, vitamin E, rosemary extract, glycerin, and triethyl citrate.

10. The molding process for disposable tableware made of biodegradable resin composite according to claim 1, characterized in that, After the hot pressing molding in step three, step four is also included: The demolded product is then subjected to post-curing treatment at 110℃-140℃ for 30-60 minutes. After the post-curing treatment, a food-grade nano wax emulsion with a solid content of 3wt%-5wt% is sprayed onto the surface of the product, with a spraying amount of 0.5g / m²-1.5g / m², forming a hydrophobic wax film with a thickness of 1μm-3μm. The food-grade nano wax emulsion is a food-grade palm wax emulsion or a food-grade carnauba wax emulsion.

Citation Information

Patent Citations

  • Bamboo blasting separation and self-recombination method

    CN108582337A